2016
DOI: 10.1097/wno.0000000000000422
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Clinical Misinterpretation and Artifacts of Optical Coherence Tomography Analysis of the Optic Nerve, Retinal Nerve Fiber Layer, and Ganglion Cell Layer

Abstract: Background:Optical coherence tomography (OCT) has become an important tool for diagnosing optic nerve disease. The structural details and reproducibility of OCT continues to improve with further advances in technology. However, artifacts and misinterpretation of OCT can lead to clinical misdiagnosis of diseases if they go unrecognized.Evidence Acquisition:A literature review using PubMed combined with clinical and research experience.Results:We describe the most common artifacts and errors in interpretation se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 69 publications
2
66
0
Order By: Relevance
“…Several studies have demonstrated that the ability to detect glaucomatous changes on OCT scans is more challenging in high myopes than emmetropes due to thinner peripapillary RNFL thickness and inaccuracies in delineating the RNFL. 23 If eyes with long axial lengths were included in this study, manual segmentation would likely perform better than automated segmentation. Studying RNFL segmentation error in eyes with higher refractive errors will be an interesting area of future study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the ability to detect glaucomatous changes on OCT scans is more challenging in high myopes than emmetropes due to thinner peripapillary RNFL thickness and inaccuracies in delineating the RNFL. 23 If eyes with long axial lengths were included in this study, manual segmentation would likely perform better than automated segmentation. Studying RNFL segmentation error in eyes with higher refractive errors will be an interesting area of future study.…”
Section: Discussionmentioning
confidence: 99%
“…In all three patients, HCQ had been used for >18 years. It is important to estimate the ocular effect of co-morbidities in the cohort analysed by Marshall et al Eyes with pathologies can also lead to increase in errors and misinterpretation of data from techniques such as SD-OCT-false-positive rates as high as 26.2% have been reported [3]. Marshall et al also report that the visual field tests were 'unreliable' (fixation losses, false positives and/or false negatives) in as many as onethird of their patients.…”
Section: To the Editormentioning
confidence: 99%
“…These have recently been outlined in more detail by Chen and Kardon. 3 First, comparisons to age-matched normative data do not fully account for important patientrelated factors. For example, myopes may have nerves which appear falsely small with corresponding pseudo-thinning of the RNFL.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%